Pengaruh Jenis Pelayanan Posyandu Terhadap Minat Ibu Balita Mengikuti Kegiatan Posyandu - Koekoeh Hardjito (Akademi Keperawatan Dharma Husada Kediri, 2015)
Integrated Health Centre (posyandu) is resourced public health efforts are managed and organized by and for the community. As a benchmark the success of the Posyandu is following the activities of community participation in Posyandu. Visits toddler is one measure of the success of the Posyandu. A visit to Posyandu toddler is inseparable from the role of mothers. A mother would be interested in visiting the neighborhood health center if the facility is in Posyandu program as expected. This study aims to analyze the influence of the type of service Posyandu against the interest mothers participated in the Posyandu. This study is a comparative observational study with cross sectional approach. Population of 120 mothers in Posyandu development / option and 320 mothers in the main Posyandu, with each sample was 93 and 188 people. Sampling technique used is proportional simple random sampling. The statistical test used was Mann Whitney test. The results showed that the interest mothers follow Posyandu in Posyandu main ministry is very interested in 82 men (43.6%) and interest in 106 (56.4%), while diposyandu service development / option is very interested in 71 (76.3 %) and interest 22 (23.7%). Mann Whitney test results demonstrate the value of p = 0.00, which means the value of P <0.05, it indicates the type of service Posyandu affect the interest mothers visit to Posyandu. Posyandu services further development is needed to increase the interest of the public to participate in the activities of Posyandu. Keywords: interest, posyandu, primary care, service development / option